2019
DOI: 10.1177/0363546519860522
|View full text |Cite
|
Sign up to set email alerts
|

Injury Surveillance in Major League Soccer: A 4-Year Comparison of Injury on Natural Grass Versus Artificial Turf Field

Abstract: Background: Artificial playing surfaces are becoming more common due to decreased cost of maintenance and increased field usability across different environmental conditions. The Fédération Internationale de Football Association (FIFA) has approved newer generation artificial turf for soccer competition at the elite level, but many elite-level athletes prefer to play on natural grass surfaces due to a perceived increase in injury rate, discomfort, and fatigability on artificial turf. Hypothesis: Injury rates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 40 publications
(95 reference statements)
1
25
0
1
Order By: Relevance
“…As mentioned above, Calloway et al 4 found no difference in the rate of total knee injuries and ACL injuries between elite soccer players competing on artificial turf versus natural grass during matches, which is in agreement with our results. In contrast, during practice, we found a higher incidence of ACL injuries on natural grass compared with artificial turf.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As mentioned above, Calloway et al 4 found no difference in the rate of total knee injuries and ACL injuries between elite soccer players competing on artificial turf versus natural grass during matches, which is in agreement with our results. In contrast, during practice, we found a higher incidence of ACL injuries on natural grass compared with artificial turf.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding soccer, a systematic review showed that artificial grass did not increase the risk of injury compared with natural grass, but study heterogeneity limited the validity of the results. 23 Calloway et al 4 recently reported no difference in overall injury rate or knee injury rate of elite soccer players who played on artificial turf versus natural grass. Similarly, in a study of elite soccer players, Ekstrand et al 7 did not find any differences in the risk of acute knee injury during practice or games based on the type of surface played.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Equivocal information exists in relation to injury literature comparing the influence of different playing surfaces during intermittent team sports. For example, previous literature has identified increased ankle injury risk on AT when compared to NT (Calloway et al, 2019), increased overall injury rates on AT when compared to NT (Mack et al, 2019), increased incidence on NT when compared to AT (Meyers 2017), or no differences in overall injury rates across playing surfaces (Steffen, Andersen, and Bahr 2007). Due to differences in methods used between studies, and the potential of contextual factors which may influence between surface comparisons, it is often difficult to develop a cause and effect relationship between surface usage and types of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Αν και η παγκόσμια ομοσπονδία ποδοσφαίρου έχει εγκρίνει νέας γενιάς τεχνητούς χλοοτάπητες για παιχνίδια υψηλού επιπέδου, οι ποδοσφαιριστές υψηλού επιπέδου προτιμούν να παίζουν σε φυσικούς χλοοτάπητες πιστεύοντας ότι στον τεχνητό χλοοτάπητα υπάρχουν περισσότερες πιθανότητες για τραυματισμό ενώ αισθάνονται μεγαλύτερη δυσφορία και κόπωση από ότι στον φυσικό. Το είδος του χλοοτάπητα λοιπόν πιθανά να είναι ένας ακόμα παράγοντας κινδύνου για τραυματισμό με τον τεχνητό να έχει κατηγορηθεί από πολλούς ότι συμβάλει περισσότερο από τον φυσικό στην εμφάνιση τραυματισμών, ωστόσο αυτό δεν έχει αποδειχθεί επαρκώς (Calloway et al, 2019;Ekstrand, Hagglund, & Fuller, 2011;Meyers, 2013Meyers, , 2017. Τέλος το επίπεδο των ποδοσφαιριστών επηρεάζει σημαντικά τόσο τον αριθμό των περιστατικών όσο και την σοβαρότητά τους με τους αθλητές χαμηλού επιπέδου να εμφανίζουν υψηλότερες συχνότητες σε σχέση με τους υψηλού επιπέδου, παρόλο που η συνολική έκθεση των χαμηλού επιπέδου αθλητών σε ποδοσφαιρικές δραστηριότητες ήταν μικρότερη (Peterson et al, 2000).…”
Section: φλεγμονή στο ποδόσφαιροunclassified